Complex Analysis and its Synergies - Krantz, Steven
Complex Analysis and its Synergies is conceived as a unique forum to showcase research and exposition in the exciting and on-going cross-fertilization of complex analysis with several other important fields of mathematics and physical sciences. The journal is an open access (OA) journal and the first pure mathematics OA journal for SpringerOpen. Complex Analysis and its Synergies has an important and distinguished Editorial Board that is dedicated to developing this new forum for cutting edge research.  Together with the considerable resources of Springer Publishing, we intend to make a mark on the field of complex analysis. The journal encourages both high-quality exposition and incisive research.  It will have special issues devoted to of-the-moment topics.  It identifies and promotes new and growing areas and validate existing ones. The journal validates and nurtures major new developments in modern complex analysis and promotes further growth in both complex analysis and those fields with which it interacts. .